Complete Genome Sequence of a Tomato Isolate of Parietaria Mottle Virus from Italy - Martínez, Carolina; Aramburu, Jose; Rubio, Luis; Galipienso, Luis (2020)
We report here the complete genome sequence of isolate T32 of parietaria mottle virus (PMoV) infecting tomato plants in Turin, Italy, obtained by Sanger sequencing. T32 shares 90.48 to 96.69% nucleotide identity with other two PoMV isolates, CR8 and Pe1, respectively, whose complete genome sequences are available.